NAVIGATING THE COMPLEXITIES OF CROSS BORDER FINANCIAL MANAGEMENT (Kashf Journal of Multidisciplinary Research, 2024)
Crossborder financial management presents unique challenges and opportunities for multinational corporations as they navigate diverse regulatory environments, currency fluctuations, and geopolitical risks. This paper provides a comprehensive analysis of the complexities associated with managing finances across borders. It explores key areas such as international financial regulations, currency risk management, transfer pricing, and tax implications. The study also examines strategies for optimizing financial performance and ensuring compliance in a global context. By drawing on case studies and recent research, the paper offers insights into effective practices for managing crossborder financial operations, highlighting the importance of strategic planning and robust financial controls.